Age Differences in Long Term Outcomes of Coronary Patients Treated with Drug Eluting Stents at a Tertiary Medical Center - Nicolas W. Shammas; Gail A. Shammas; Peter Sharis; Michael Jerin (Journal of Aging Research)
We evaluate differences in outcomes in younger (<65 years) and older (≥65 years) patients for target lesion failure (TLF) at 2-year follow-up in an unselected consecutive series of patients treated with the everolimus- (EES) and paclitaxel-eluting (PES) stents at a tertiary medical center. 348 consecutive patients (younger 150; older 198) stented with the EES and PES were retrospectively analyzed. The primary endpoint was TLF (composite endpoint of cardiac death, non fatal myocardial infarction due to index vessel and target lesion revascularization (TLR)). At 2 years follow up, younger versus older patients had the following outcomes respectively: TLF 27.7% versus 25.5% (P=0.71), TLR 24.8% versus 21.4% (P=0.52), cardiac death 3.4% versus 2.5% (P=0.75) and definite and probable stent thrombosis (2.0% versus 1.0%). Multivariate analysis showed that renal failure (odds ratio: 2.55, P=0.045), number of stents per patient (odds ratio: 1.60, P=0.001) and younger age (odds ratio: 0.97; P=0.010), but not gender, diabetes or type of DES stent (EES versus PES) predicted TLF. We conclude that older age was not a predictor of TLF at 2-year follow-up after adjusting for renal insufficiency, number of stents used per patient, gender, diabetes and type of DES used.